Some Biological Characteristics of Luciobarbus esocinus Heckel, 1843 Living in Keban Reservoir - Coban, Mehmet Zulfu; Turkgulu, Ibrahim; Yuksel, Fahrettin; Celayir, Yasin; Yuce, Songul; Eroglu, Mucahit; Sen, Dursun (Central Fisheries Research Inst, 2012)
This study was carried out in Luciobarbus esocinus obtained from Keban Reservoir (Elazig) between March 2008 and October 2009. During the research, it was determined that the percentage of male, female and undefined individuals from 187 L. esocinus were 45.46%, 37.43% and 17.11% respectively. The ages of population were distributed between I and XVII. The lengths of the individuals ranged from 23.0 to 112.4 cm and the weight of them ranged from 118 to 18,042 g. The length and weight equation for population was determined as W-all individuals = 0.0057*TL3.2187 (n= 187, r= 0.98). The highest GSI values of both sexed were obtained in March and these values were decreased rapidly after this month. It was determined that the condition factor increased until age 5 and then, it decreased respectively.
Keban baraj gölünde yaşayan Luciobarbus esocinus Heckel, 1843'ün bazı biyolojik özellikleri
Keywords: Luciobarbus esocinus; growth; GSI; length-weight relationship; condition factor